Political exhaustion and the experiment of street: Boyle meets Hobbes in Occupy Madrid. (16th March 2017) - Corsín Jiménez, Alberto; Estalella, Adolfo
Abstract : This essay describes the complex negotiations around stranger sociability, public space, and democratic knowledge that shaped the meetings of popular assemblies in the wake of the Spanish 15M/Occupy movement. The work of assembling was 'exhausting', by which participants would mean two things. In one sense, meetings would often turn into tiresome affairs, trying the patience and resilience of participants. In another sense, attendants would describe assemblies as spaces of political 'exhaustion', where politics as usual was emptied out and replaced by new democratic possibilities. We offer here an account of exhaustion as an ethnographic category. We are particularly interested in the role accorded to exhaustion as a vacuum enabling the appearance of novel social and political roles. We develop our argument by drawing a provocative analogy with the early history of scientific experimentation, where the nature of an 'assembly' of trusted peers and its location in genteel space became constitutive of a new type of experimental knowledge. What social and epistemic figures are popular assemblies bodying forth today?